Pollen limitation, plasticity in floral traits, and mixed mating system in an alpine plant Pedicularis siphonantha (Orobanchaceae) from different altitudes. Issue 3 (7th March 2017) - Dai, Wen‐Kui; Kadiori, Edwin Luguba; Wang, Qing‐Feng; Yang, Chun‐Feng
Abstract: Plant mating systems rapidly respond to pollen limitation in changing environments. However, whether and how floral traits are involved in a mating system shift requires further investigation. A widely distributed and bumblebee‐pollinated lousewort, Pedicularis siphonantha D. Don was studied. We investigated pollination systems, reproductive success, and floral traits in four large populations growing from 3200 m to 4300 m. Pollinator activity in low altitude populations was lower and these populations had a decreased fruit set and seed number per capsule compared to populations at high altitudes. Supplemental hand pollination with outcross pollen significantly increased seed production per capsule for plants from high altitudes but not for those from lower altitudes. We also found that bumblebees visited more flowers within an inflorescence in a single foraging bout in high altitudes compared with low altitudes, which caused a high possibility of geitonogamous mating. These differences may be pollination‐dependent rather than inheritance‐based because hand pollination on bagged flowers did not cause a difference in seed production across populations. Compared to plants from low altitudes, high‐altitude plants had increased flower longevity, larger floral displays, higher pollen production per flower, and shorter corolla tubes, which were found to be well in accordance with changes in both pollination environment and mating system. Plasticity in floral traits might help plants to adjust their resource allocation strategies in response to their habitat, which might be linked with pollination environment. The variability among these populations might be beneficial for this widely distributed species to cope with environmental changes.